2017
DOI: 10.1111/his.13369
|View full text |Cite
|
Sign up to set email alerts
|

PNL2: an adjunctive biomarker for renal angiomyolipomas and perivascular epithelioid cell tumours

Abstract: PNL2 has high sensitivity and specificity for AML and PEComas as compared with non-MiTF renal tumours, and PNL2 appears to be a more useful biomarker for sclerosing and malignant PEComas. For cases that are limited in tissue quantity (i.e. core biopsies) and/or are morphologically suspicious for AML/PEComa, but negative or focally positive for HMB45 and melan-A, PNL2 may be a useful adjunctive biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The majority of EAML cases display membranous and cytoplasmic staining of E-cadherin, whereas classic AML cases demonstrate cytoplasmic staining alone (20). Moreover, in diagnostically challenging cases, staining for CD68 (PG-M1) (21) and PNL2 (22) may be helpful in distinguishing renal EAML form other renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of EAML cases display membranous and cytoplasmic staining of E-cadherin, whereas classic AML cases demonstrate cytoplasmic staining alone (20). Moreover, in diagnostically challenging cases, staining for CD68 (PG-M1) (21) and PNL2 (22) may be helpful in distinguishing renal EAML form other renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Among additional PEComa markers cathepsin K is mentioned; its expression was observed in all analysed cases [45,47], and transcriptional factor TFE3 (transcription factor binding to IGHM enhancer 3) was observed in 29-38% of cases regardless of the rearrangement of the TFE3 gene [36,44]. PNL2 has been proposed as a new marker with high sensitivity and specificity in the differentiation of PEComa and AML (expression described in 89% of cases) from other neoplasms derived from kidneys, which do not express this marker [48]. In immunohistochemical analysis PEComas also stain positive for vimentin, CD-31, and CD-34 and are negative for CgA (chromogranin A), Syn (synaptophysin), CK (creatine kinase), CD117, CD10, AFP (alpha-fetoprotein), and EMA (epithelial membrane antigen).…”
Section: Pathomorphologymentioning
confidence: 97%
“…Caliò et al also proposed that parvalbumin is expressed in many cases and can even be used as an immune marker for EAML lesions 41 . Moreover, PNL2 has been shown to be a biomarker of sensitivity and specificity in melanoma; recently, some scholars have found that compared with HMB‐45, PNL2 has a higher sensitivity for differentiating PEComa from other renal tumors (85% vs. 81%) and has specificity in malignant PEComa (89% vs. 81%) 42 …”
Section: Diagnosis Of Renal Epithelioid Angiomyolipomamentioning
confidence: 99%
“…41 Moreover, PNL2 has been shown to be a biomarker of sensitivity and specificity in melanoma; recently, some scholars have found that compared with HMB-45, PNL2 has a higher vs. 81%) and has specificity in malignant PEComa (89% vs. 81%). 42…”
Section: Histopathological Examinationmentioning
confidence: 99%